2001
DOI: 10.1038/35101627
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in Pseudomonas aeruginosa biofilms

Abstract: Bacteria often adopt a sessile biofilm lifestyle that is resistant to antimicrobial treatment. Opportunistic pathogenic bacteria like Pseudomonas aeruginosa can develop persistent infections. To gain insights into the differences between free-living P. aeruginosa cells and those in biofilms, and into the mechanisms underlying the resistance of biofilms to antibiotics, we used DNA microarrays. Here we show that, despite the striking differences in lifestyles, only about 1% of genes showed differential expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
850
8
11

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,054 publications
(912 citation statements)
references
References 27 publications
(11 reference statements)
33
850
8
11
Order By: Relevance
“…However, mutational analysis and gene expression studies of genes that encode known drug efflux pumps indicated that this is not necessarily the case [30,32]. A comparison of the RNA expression profiles from P. aeruginosa planktonic cultures and biofilms identified several candidate genes that may contribute to the antibiotic resistance phenotype of biofilm cells [33]. For example, increased expression of the tolA gene is hypothesized to alter the structure of lipopolysaccharides in the outer membrane, making it more difficult for aminoglycoside antibiotics, such as tobramycin and gentamicin, to enter the cell.…”
Section: Physiology-dependent Resistancementioning
confidence: 99%
“…However, mutational analysis and gene expression studies of genes that encode known drug efflux pumps indicated that this is not necessarily the case [30,32]. A comparison of the RNA expression profiles from P. aeruginosa planktonic cultures and biofilms identified several candidate genes that may contribute to the antibiotic resistance phenotype of biofilm cells [33]. For example, increased expression of the tolA gene is hypothesized to alter the structure of lipopolysaccharides in the outer membrane, making it more difficult for aminoglycoside antibiotics, such as tobramycin and gentamicin, to enter the cell.…”
Section: Physiology-dependent Resistancementioning
confidence: 99%
“…However, the nature of the signals that trigger the prophages to enter the lytic cycle during biofilm formation in S. oneidensis is thus far unknown. Notably, phage genes have been shown to be strongly upregulated in biofilms of several bacterial species (Whiteley et al, 2001;Ren et al, 2004;Domka et al, 2007). It remains to be shown whether phage induction in S. oneidensis MR-1 is a direct response to surface attachment and/or nutrient limitations as indicated by cell lysis occurring in planktonic cultures in late exponential phase and whether the prophages are also involved in the dispersal of S. oneidensis biofilms.…”
Section: Mutants Lacking the Prophages Are Defective In Biofilm Formamentioning
confidence: 99%
“…These features were surprising since we often naturally assume that many biofilm cells would be under nutrient limitation (no matter the flow rate) and, accordingly, the cells should not look so healthy. Yet studies do suggest strong metabolic activity (57), and recent DNA microarray studies reveal ribosomal gene expression to be upregulated in P. aeruginosa, Escherichia coli, and B. subtilis biofilms versus their planktonic counterparts (60,62,69).…”
mentioning
confidence: 99%